2022
DOI: 10.1007/s10900-022-01069-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Undiagnosed Hypertension Among Chinese and Korean American Immigrants

Abstract: Asian Americans are more likely to be unaware that they have hypertension compared to non-Hispanic white Americans, despite having higher risk of hypertension at lower body-mass indices. Furthermore, immigrants are more likely than their United States (U.S.)-born counterparts to have undiagnosed hypertension, placing them at greater risk of subsequent morbidity and mortality. This study examines the social determinants of undiagnosed hypertension among Asian American immigrants. Using a study of foreign-born C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…The current systematic review and meta-analysis revealed that the pooled prevalence of undiagnosed hypertension in Ethiopia was 18.26% (95% CI 14.94, 21.58). This finding is comparable with those studies conducted on rural Ruanda18.7% [ 34 ], Chinese and Korean American immigrants (14.5%) [ 35 ], and United Kingdom patients (17%) [ 36 ]. This finding implies that strengthening the identification rate for undiagnosed hypertension is required.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current systematic review and meta-analysis revealed that the pooled prevalence of undiagnosed hypertension in Ethiopia was 18.26% (95% CI 14.94, 21.58). This finding is comparable with those studies conducted on rural Ruanda18.7% [ 34 ], Chinese and Korean American immigrants (14.5%) [ 35 ], and United Kingdom patients (17%) [ 36 ]. This finding implies that strengthening the identification rate for undiagnosed hypertension is required.…”
Section: Discussionsupporting
confidence: 89%
“…The pooled odds of developing undiagnosed hypertension were approximately four times higher among the older adults than among the younger study participants. This finding is supported by studies of Chinese and Korean American Immigrants [ 35 ], Bangladesh [ 19 ], the Central Africa Republic [ 40 ], Nigeria [ 39 ] and Sudan national survey . [ 41 ] This is explained by the fact that as people agedthey are more likely to develop chronic illnesses such as hypertension.…”
Section: Discussionsupporting
confidence: 58%
“…Emigration studies may provide some insight into genetic versus environmental determinants of hypertension within an ethnic group. However, studies of Asian people emigrating to the USA have noted that access to healthcare and insurance status are the most important determinants of BP diagnosis and control [ 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among Asian Americans, although the research is minimal, growing evidence suggests higher rates of car diovascular disease relative to their European American counterparts (Jose et al, 2014). To highlight the scarcity of this literature, to our knowledge only one recent study demonstrated that Asian Americans have increased risk for undiagnosed hypertension as compared to their European American counterparts (Morey et al, 2022). It may be that the prevalence of cardiovascular disease in this population is underdiagnosed (Narayan et al, 2010) and therefore warrants further study.…”
Section: Perseverative Cognition: Implications For Cardiovascular Healthmentioning
confidence: 94%